Effect of postconditioning on infarct size in patients with ST elevation myocardial infarction. Issue 21 (18th October 2010) - Sörensson, Peder; Saleh, Nawzad; Bouvier, Frederic; Böhm, Felix; Settergren, Magnus; Caidahl, Kenneth; Tornvall, Per; Arheden, Håkan; Rydén, Lars; Pernow, John
Abstract : Background: Small studies suggest that postconditioning reperfusion interrupted by brief repetitive cycles of reocclusions, may protect the myocardium in the clinical setting. Objective: To test the hypothesis that postconditioning limits infarct size in relation to the area at risk in patients with ST elevation myocardial infarction (STEMI). Methods: 76 patients (aged 37–87 years) eligible for primary percutaneous coronary intervention due to STEMI were randomised to standard percutaneous coronary intervention (n=38) or postconditioning, consisting of four cycles of 60 s reperfusion and 60 s of reocclusion before permanent reperfusion (n=38). Results: The area at risk was determined from angiographic abnormally contracting segments. Infarct size was quantified from delayed enhancement MRI on days 6–9. Infarct size, expressed in relation to the area at risk, did not differ between the control group (44%; 30, 56) (median and quartiles) and the post-conditioned group (47%; 23, 63). The slope of the regression lines relating infarct size to the area at risk differed between the two groups. Infarct size was significantly (p=0.001) reduced by postconditioning in patients with large areas at risk. The area under the curve and peak troponin T release and CKMB during 48 h did not differ between patients in the control and postconditioning groups. Conclusions: This prospective, randomised trial suggests that postconditioning does not reduce infarct size in patients with STEMI in the overall study group. The data indicate that postconditioning may be of value in patients with large areas at risk. Clinical trial registration information: Karolinska Clinical Trial Registration (http://www.kctr.se ). Unique identifier: CT20080014.